Status of oxidative stress biomarkers and lecithin cholesterol acyltransferanse (LCAT) gene variant in subjects with low HDL-c concentration / Farah Hanis Sakri - Sakri, Farah Hanis (2016)
Oxidative stress has been established as a key event in initiation and progression of atherosclerosis. Oxidized low density lipoprotein (ox-LDL), F₂₋isoprostanes (F₂₋iPs), and malondialdehyde (MDA) are biomarkers reflecting the status of oxidative stress. High-density lipoprotein cholesterol (HDL-c) is protective against atherosclerosis and coronary heart disease (CHD), but its association with oxidative stress is not well established. Studies have indicated that 40-60% of the variation of HDL-c concentration is genetically determined. Extensive literature search indicates that mutation in lecithin cholesterol acyltransferase (LCAT) gene is reported to be associated with lowering of HDL-c concentration. However, there is scarcity of such data amongst the Asian population particularly in a Malay-dominated community. Thus, this study aimed to a) compare the concentration of oxidative stress biomarkers between low HDL-c subjects and normal controls, b) examine the correlation and association between HDL-c and these biomarkers, c) investigate whether HDL-c concentration is an independent predictor for these biomarkers and d) determine the genetic variants of LCAT. A total of 207 low HDL-c subjects and 215 normal controls were recruited for the biochemical aspect of the study. For genetic studies, 70 subjects with the lowest deciles of HDL-c and 140 normal controls were selected from the recruited samples. All exons of LCAT were PCR amplified and sequenced in both groups. For both studies, the groups were matched for age, gender, ethnicity, smoking status, diabetes and hypertension. It was found that oxidative stress biomarkers were higher in low HDL-c group compared to normal controls. There were negative correlations and association between HDL-c concentration and some of the biomarkers. HDL-c was not an independent predictor for the biomarkers. All exons sequencing of LCAT gene revealed no variant found in the subjects studied. In conclusion, HDL-c concentration is strongly associated and correlated with status of oxidative stress, which in part explains the pathogenesis of atherosclerosis associated with low HDL-c. However, it is conceivable to speculate that the role of LCAT variation in HDL-c concentration may be minimal in our population.